Peningkatan Kemampuan Guru Menggunakan Alat Permainan Edukatif (APE) Melalui Supervisi Kunjungan Kelas di 2 TK Binaan Kota Bandar Lampung - Marliani, Marliani (CV. Creative Tugu Pena, 2022)
The purpose of this classroom action research was to improve the teacher's ability in using educational game tools through visiting class. This research is a school action research with four main steps, namely: planning, implementation, observation and reflection. The research subjects were teachers in 2 TK under the guidance of the city of Bandar Lampung, which consisted of 10 teachers. Data collection techniques using observation and documentation techniques. Data validation with triangulation technique. The method uses qualitative data analysis. The results of the research on the ability of teachers in the initial conditions reached an average number of 57.62 with less criteria and the first cycle increased to 68.33 in sufficient criteria and in the last cycle to 80.43 in very good criteria. Individually per teacher in the initial conditions nothing has been completed, increased to 5 teachers or 50% and in the last cycle to 10 teachers or 100% and the implementation of learning in the initial conditions reached an average number of 59.17 with less criteria and the first cycle increased to 69.44 in the sufficient criteria and in the last cycle to 83.75 in the very good criteria, and individually per teacher in the initial condition not yet completed, increasing to 3 teachers or 30% and in the last cycle to 10 teachers or 100%. The conclusion is that the implementation of supervision with the class visit technique has been proven to be able to improve the ability of teachers in the 2 TK assisted by Bandar Lampung City in Semester 2 of the 2021/2022 Academic Year in the use of educational game tools (APE). Keywords: Educational Game Tool, Visiting Class Supervision, Increasing Teachers’ Ability